2011
DOI: 10.1149/1.3598141
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Microstructure, Ionomer Property and Proton Transport in Pseudo Catalyst Layers

Abstract: The influence of the ionomer content on proton transport phenomena in the catalyst layers of a fuel cell was examined using pseudo catalyst layers (PCLs) consisting of the carbon support and the ionomer. Effective proton conductivity r eff of the PCL increased with increasing ionomer content in both graphitized ketjen black (GKB) and ketjen black (KB) systems. It was found that the ionomer coverage h and the Bruggeman factor c, which is related to the tortuosity of the proton path in the PCL, did not depend on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 25 publications
4
53
0
Order By: Relevance
“…As 2 and 3 layers of nodes are used in the simulations, the effective conductivity behavior quickly approaches that of the 3-D case. This is also in qualitative agreement with the existing experimental observations [76][77][78][81][82][83][84][85][86][87][88], which show conductivity approaching the bulk value for thicknesses above 100 nm or so.…”
Section: Nafion-inspired Networksupporting
confidence: 92%
See 1 more Smart Citation
“…As 2 and 3 layers of nodes are used in the simulations, the effective conductivity behavior quickly approaches that of the 3-D case. This is also in qualitative agreement with the existing experimental observations [76][77][78][81][82][83][84][85][86][87][88], which show conductivity approaching the bulk value for thicknesses above 100 nm or so.…”
Section: Nafion-inspired Networksupporting
confidence: 92%
“…Finally, it is of interest to examine possible proton conduction through interfacial structures or Nafion thin-films that exist within PEFC catalyst layers, where these thin films form a 3D network throughout the layer in which protons must travel [80]. These thin-films demonstrate reduced conductivity and water uptake [76][77][78][81][82][83][84][85][86][87][88] and can limit PEFC performance at low catalyst loadings as discussed recently [89], and the modeling of such transport in thin-films is of active interest [1]. It is well known that when a polymer is confined to thicknesses comparable to its characteristic domain size, its properties and morphology differ from the analogous bulk materials [90].…”
Section: Nafion-inspired Networkmentioning
confidence: 99%
“…As shown in Figure 20, water-uptake isotherms for Nafion in the catalyst layers show much lower water contents compared to bulk Nafion membrane. 157 Also, water uptake in catalyst layers has been shown to increase with increasing loading of platinum, which improves wetting properties and hydrophilicity, 157,326 and with increasing ionomer content, 326,327 although in general the catalyst layer's ionomer water uptake has been consistently shown to be depressed. 157,327 With the lower water contents (and perhaps the existence of different morphology and confinement driving the lower water uptake), it is not surprising that the ion conductivity is likewise depressed, [327][328][329] and is a function of ionomer content.…”
Section: Catalyst-layer Modelingmentioning
confidence: 99%
“…4 Ex-situ measurements on thin-film ionomer performed by several groups have shown that the ionomer nanostructure and its properties such as water uptake, proton conduction, and O 2 permeability can vary substantially depending on its thickness, treatment history, and substrate interaction. [9][10][11][12][13][14][15][16][17] Furthermore, sulfonate groups in the ionomer can adsorb on a Pt surface and reduce the oxygen reduction reaction (ORR) activity. 18,19 Because the adsorption of the acid group immobilizes the ionomer to the Pt surface, [20][21][22] it is surmised that it will also increase O 2 transport resistance.…”
mentioning
confidence: 99%